The Influence of Entrepreneurial Competence, Motivation and Innovation on SMEs Performance - Fitri Masraya Siregar; Zulkifli Musannip Efendi Siregar; Pitriyani Pitriyani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study is intended to determine the effect of entrepreneurial competence, motivation, and innovation on the performance of MSME at a coffee shop in Ajamu, Panai Hulu Subdistrict, Labuhanbatu Regency. This research was conducted at a coffee shop in Ajamu by taking a sample of 160 respondents. The results of research that have been conducted indicate that entrepreneurial competence, motivation, and innovation affect the performance of MSME at coffee shops. This study uses a non-probability method in the form of incidental and purposive sampling. this study, using the normality test and path analysis techniques with the help of the Amos software application. The results of the study found 1) Entrepreneurial competence has no positive and significant effect on innovation. 2) Motivation has a positive and significant effect on innovation. 3) Entrepreneurial competence has a positive and significant effect on MSME performance. 4) Motivation has a positive and significant effect on MSME performance. 5) Innovation has a positive and significant effect on MSME performance